PERANAN APLIKASI MOTHER CARES (MOCA) TERHADAP KEPATUHAN ORANGTUA DALAM MELAKUKAN STIMULASI TUMBUH KEMBANG ANAK - Tarigan, Eka Falentina (Midwifery And Complementary Care, 2022)
Background: Based on data from the Basic Health Research (Riskesdas) in 2018, there are 30.8% of children under five in Indonesia experiencing stunting or as many as 1 in 3 babies under 2 years or around 9 million children suffering from stunting. This prevalence decreased by 6.4% from 2013 (37.2%). The data for 2021 (24.4%) and 2019 (27.7%) even though it decreased but did not significantly achieve the SDGs target. There are 16% of Indonesian toddlers experiencing developmental disorders, both fine and gross motor development, hearing loss, less intelligence and developmental delays . Objective:. The purpose of this study was to analyze the role of the Mother Cares (MOCA) application on parental compliance in stimulating the growth and development of children aged 18-24 months. Methods: The research design is quantitative with an analytical approach using a quasi-experimental design with a pre-post test design. The population in this study were parents who had children aged 18-24 months. Result: The median value of knowledge is 84.0 and 84.2 on skills after being given the intervention while the median value in the control group is 72.0 on knowledge and 73.7 on skills. The increase in knowledge was 8.0 in the intervention group and 4.0 in the control group and there was the same increase in skills in both groups, namely 21.05. The median value of the intervention group was 89.0 on gross motor, 118.0 on fine motor, 97.0 on speech and language and 139.0 on independence and socialization while the control group did not meet the criteria for compliance with a median value of 15.0 on fine motor. , 16.0 on gross motor, 15.0 on speech and language and 15.0 on independence and socialization, with a Relative Risk value of 2.2 Conclusion: There is a role for the application of Mother Cares (MOCA) to increase parental compliance in stimulating children's growth and development with an increase in compliance of 2.2 times in the intervention group compared to the control group. Keywords: Mother Cares (MOCA) Application, Compliance, Stimulation of Child Development.